2020
DOI: 10.1016/j.ijid.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A single holiday was the turning point of the COVID-19 policy of Israel

Abstract: Highlights Israel has led a successful mitigation policy until mid-March 2020. The policy collapsed abruptly following a holiday of public gatherings. Analysis: transmission chains, local to imported cases time series and SEQIJR dynamical model. No evidence for significant contribution of super-spreaders. Even short lapse in public responsiveness can dramatically affect public health.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…Particularly, it meant that older age groups who would usually be less risk averse in terms of social distancing, etc., would be meeting younger age groups where incidence was highest. Similar experiences have been observed in USA, Israel, China and elsewhere, which demonstrated that festive holidays, which tend to draw individuals from distant places into close contact for prolonged periods, are associated with a spike in COVID-19 incidence [ 32 , 33 , 34 ]. This naturally increases the chance of introduction of new strains, e.g., B.1.1.7 [ 35 ].…”
Section: Discussionsupporting
confidence: 68%
“…Particularly, it meant that older age groups who would usually be less risk averse in terms of social distancing, etc., would be meeting younger age groups where incidence was highest. Similar experiences have been observed in USA, Israel, China and elsewhere, which demonstrated that festive holidays, which tend to draw individuals from distant places into close contact for prolonged periods, are associated with a spike in COVID-19 incidence [ 32 , 33 , 34 ]. This naturally increases the chance of introduction of new strains, e.g., B.1.1.7 [ 35 ].…”
Section: Discussionsupporting
confidence: 68%
“…The characteristics of the selected articles are listed in Supplementary Table S3 . Among the 60 estimates of transmission heterogeneity, four (6.7%) from two studies estimated the dispersion parameter ( k ) of SARS [16] , [18] , 11 (18.3%) from eight articles estimated the k for MERS [16] , [17] , [30] , [31] , [32] , [33] , [34] , [35] , and 45 (75.0%) from 17 articles estimated the k for COVID-19 [14] , [15] , [19] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] . Forty estimates (66.7%) were based on transmission pair data (i.e., offspring case number generated by each index case), and four estimates were calculated using epidemic/cluster size data.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five estimations (41.7%) reported only k without the other two measures [33] , [41] , [43] , [46] , [49] , [50] . We conducted a secondary analysis to generate an estimated k value for seven articles that reported the ‘20/80’ rule [31] , [32] , [34] , [35] , [40] , [43] , [44] instead of a k value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model allows to simulate the impact of these measures and make comparison with the evolution without intervention. We hope authorities will use this tool, in addition to established venues [ 8 , 61 ], to simulate different lockdown policies for choosing the best exit strategy [ 62 ].…”
Section: Discussionmentioning
confidence: 99%